Globally optimal trial design and risk sharing arrangements are key to avoiding opportunity costs of delay and enabling equitable, feasible and effective global vaccine research and implementation in current or future pandemics - Eckermann, Simon (Frontiers in Public Health, 2022)
Global vaccination in the face of pandemics such as COVID-19 are a race against time and new variants, where the key challenge and imperative is to avoid opportunity costs of delay and associated health, social and economic downstream impacts. Failures to address global challenges with COVID-19 have become increasingly evident as waves of vaccine evading mutations have evolved over time, facilitated by globally inequitable vaccination coverage and associated immunity waning against new variants globally. Addressing those challenge requires better aligning societal decision maker (governments) and industry manufacturer interests for fast globally optimal trial design. Ideally, with research coverage, implementation and accessibility of effective vaccines across joint research, implementation and distribution cycles in addressing pandemic evolution in real time. Value of information (VoI) methods for optimal global trial design and risk sharing arrangements are shown to align research, distribution and implementation interests and efforts globally to meet head on the imperative of avoiding opportunity costs of delay and enable effective global solutions consistent with maximising local and global net benefit. They uniquely enable feasible early adoption of the most promising strategies in real time while best globally translatable evidence is collected and align interests to globally distribute and implement. Further, these methods are more generally shown as imperative for feasible, fast and optimal solutions across joint research, reimbursement and regulatory processes for current and future pandemics and other global existential threats. Establishing pathways for globally optimal trial designs, risk sharing agreements and efficient translation to practice is urgent on many fronts.